AN ANALYSIS OF ID AND EGO NOVEL “A TALE OF TWO CITIES” BY CHARLES DICKENS - Romanna; Rudianto, Gaguk (JEE (Journal of English Education), 2020)
This study aims to describe the id and ego of the characters in the novel A Tale of Two Cities by Charles Dickens using the approach of psychological approach. This type of research is a qualitative descriptive study and the data obtained from this study produce a psychological analysis in the Charles Dickens novel entitled "A Tale of Two Cities". There are two psychiatric structures that are described in this study, namely the id and the ego using the theory of Sigmund Freud.